Effect of sowing time on phytomass production during early growth of two varieties of Stylosanthes guianensis (Aubl.) Sw. - Paterniani, MLS; Rodrigues, TJD; Pereira, G. T.; Rodrigues, LRA (Fundação Estudos Agrarios Luiz Queiroz (fealq), 2001)
The objective of this research was to determine the effect of two sowing times on phytomass production of two varieties of Slylosanthes guianensis (var. pauciflora and var. vulgaris). Two experimental periods were studied (1: January - May/1998 and 2: November/1998 - March/1999) using a completely randomized factorial design 2 x 2 x 14 (two periods, two varieties and fourteen ages of evaluation), with four replications. The results showed a difference between the periods concerning the growth and development of Stylosanthes, and that period 2 was the most favourable to this forage plant. There was, also, different adaptability between the two varieties concerning the sowing times. The var. pauciflora was more adapted in period 1, and the var. vulgaris, in period 2. The data showed the possibility of selecting Stylosanthes cultivars adapted to different seasonal conditions.
Keywords: stylo; dry mass; forage physiology